Previdência Social no Rio Grande do Sul : cenários e interfaces com a saúde do trabalhador - Galvão, Aline Aiko Yoshida (2015)
This dissertation analyzes the relationship between the organization and division of labor and the worker's health-disease process, through the work profile mapping at the National Institute of Social Security (INSS), in the state of Rio Grande do Sul. The construction of this work took place through research, whose problem was initially designed to investigate how the Social Security in the state of Rio Grande do Sul is organized as its active workers. During the research, the data and analysis that emerged brought more complex findings and deepened the discussion on the relationship between work in the context of corporate restructuring resulting from the neoliberal advance from the 1980s to expand the understanding the categories of analysis, theoretical approach was needed on the concept of work, which was revealed in its centrality as construction mode and reproduction of human sociability of structural and cyclical changes in production methods, Social Security and its historic building within the various social protection concepts according to the state of existing models from the conservative models to the design of the Welfare State, and the process of construction and development of Occupational Health concept in Brazil, since the conventional hospital-centered model until its transformation from the Sanitary Reform Movement. The research, which aims to translate into support new studies and action plans on the subject of workers' health, used the approach of the socio-historical and dialectical view of social reality which provided bases to analyze, within the categories of the dialectical method of how the relationship between the state and the capital historically determined the design of social protection to the working class, the conflicting relations between the State of Social Welfare and the managerialist model of state, whose logic is transferred from the private to the public and that worsens the relationship between capital and work, and how this process of alienation constitutes a universal phenomenon among workers in the context of the flexible accumulation capitalism breakthrough that resulted in the movement of the state reform backset. The documentary research appreciated the expansion of understanding of the object in its historical and sociocultural context, making relevant source for concrete mapping to be performed. In the context of theoretical discussion and analysis of the data, mapping the capacity of the INSS servers in Rio Grande do Sul warned of a next scenario of shortage of workers, since the count of the number of servers by the Social Security Agency considers a large portion of which is in Permanence Allowance, and selection processes information are insufficient to assess whether the division of labor in the INSS is healthy, making it important to discuss the relationship between overload, or surplus, and the illness. The changes in the activity carried out Taylorization type undergo a process at the same time as the public service undergoes a Toyotist demand for flexibility, shows the scene of alienation and loss of meaning of work, compounded by the implementation of goals and performance evaluations, making the INSS server subject overload and physical and mental illness. This research also highlights the challenge of working class is fragmented by new management models and who cannot find space for reflection on the work as a determinant of health.